Mental Health and Substance Use Care Among Young Adults Before and After Affordable Care Act (ACA) Implementation: A Rural and Urban Comparison. Issue 1 (7th July 2017) - Chavez, Laura J.; Kelleher, Kelly J.; Matson, Steven C.; Wickizer, Thomas M.; Chisolm, Deena J.
Abstract: Purpose: Rural young adults experience greater unmet need for mental health (MH) and alcohol or drug (AOD) treatment and lower health insurance coverage than urban residents. It is unknown whether Affordable Care Act (ACA) reforms in 2010 (dependent coverage extended to age 26) or 2014 (Medicaid expansion) closed rural/urban gaps in insurance and treatment. The present study compared changes in rates of health insurance, MH treatment, and AOD treatment for rural and urban young adults over a period of ACA reforms. Methods: Young adult participants (18‐25 years) in the National Survey on Drug Use and Health (2008‐2014) with past‐year psychological distress or AOD abuse were included. Difference‐in‐differences logistic regression models estimated rural/urban differences in insurance, MH, and AOD treatment pre‐ versus post‐ACA reforms. Analyses adjusted for gender, race, marital status, and health status. Results: Among 39, 482 young adults with psychological distress or AOD, adjusted insurance rates increased from 72.0% to 81.9% (2008‐2014), but a significant rural/urban difference (5.1%) remained in 2014 ( P < .05). Among young adults with psychological distress (n = 23, 470), MH treatment rates increased following 2010 reforms from 30.2% to 33.0%, but gains did not continue through 2014. Differences in MH treatment over time did not vary by rural/urban status and there were no significant changes in AOD treatment for either group. Conclusions: Although rates of insurance increased for all young adults, a significant rural/urban difference persisted in 2014. Meaningful increases in MH and AOD treatment may require targeted efforts to reduce noninsurance barriers to treatment.